Nanowires: Cobalt‐Doping in Molybdenum‐Carbide Nanowires Toward Efficient Electrocatalytic Hydrogen Evolution (Adv. Funct. Mater. 31/2016). (August 2016) - Lin, Huanlei; Liu, Ning; Shi, Zhangping; Guo, Yulin; Tang, Yi; Gao, Qingsheng
Abstract : Effective electron modulation on metal‐carbides is essential for exploring noble‐metal‐free electrocatalysts for hydrogen evolution reactions (HER). On page 5590, Y. Tang, Q. S. Gao, and co‐workers report an effective cobalt‐doping to increase the electron density around Fermi level in Mo2 C nanowires, accomplishing high activity, striking kinetic metrics and good durability for HER in both acidic and basic electrolytes.